2018
DOI: 10.3390/su10051386
|View full text |Cite
|
Sign up to set email alerts
|

The Carbon Impact of International Tourists to an Island Country

Abstract: Taiwan, located in the East Asia, is an island country with limited natural resources. To increase economic growth and reduce CO 2 emission levels, the Taiwanese government is promoting a sustainable low-carbon tourism industry. This study investigated the CO 2 emission coefficient of tourist activities and identified the CO 2 emissions (CE) patterns of international visitors to Taiwan. The total CO 2 emission per visitor without considering international transportation was estimated using a questionnaire. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Tourists are the most important participants in and experiencers of tourism and travel [28]. Numerous tourist-based studies on tourism impacts have been conducted [23][24][25][26][27][28][29][30][31]; it was found that tourists also have varying opinions about the changes caused by tourism development.…”
Section: Analysis and Review Of Related Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Tourists are the most important participants in and experiencers of tourism and travel [28]. Numerous tourist-based studies on tourism impacts have been conducted [23][24][25][26][27][28][29][30][31]; it was found that tourists also have varying opinions about the changes caused by tourism development.…”
Section: Analysis and Review Of Related Studiesmentioning
confidence: 99%
“…The residents hope that tourism-driven improvements in business investment and earnings will meet their expectations. If the living needs of the residents cannot be met, this will lead to a divergence between each stakeholder in their opinions about the following tourism-related economic issues: job opportunities, opportunities for starting a new business, opportunities for working as a tour guide, policies on tourism protection, and designing creative commodities [9,11,12,[23][24][25][26][27][28][29][30][31].…”
Section: Economic Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Human activities are affecting the Earth's system with unprecedented magnitude and speed, which, in turn, affects the quality of human life and the level of sustainable development. Tourism is closely linked to the environment and climate and is considered to be a vulnerable and highly climate-sensitive sector of the economy [1,2]. According to the research report of the World Tourism Organization, the carbon dioxide generated by global tourism development reached 1.3 billion tons, which accounted for 4.9% of the total anthropogenic carbon dioxide, while the contribution rate of anthropogenic global warming by the tourism sector accounted for 5-14% [3,4].…”
Section: Introductionmentioning
confidence: 99%